Genome-wide identification and expression analysis of GRAS transcription factors under cold stress in diploid and triploid Eucalyptus - Liu, Jiannan; Chen, Hao; Li, Chenhe; Du, Kang; Yang, Jun (Frontiers in Genetics, 2025)
The GRAS [GRI (Gibberellic Acid Insensitive), RGA (Repressor of GAI-3 mutant), and SCR (Scarecrow)] transcription factors play a pivotal role in the development and stress responses of plants. Eucalyptus is an important fast-growing tree species worldwide, yet its poor cold tolerance limits its cultivation range. This study conducted a bioinformatics analysis of Eucalyptus grandis GRAS family and investigated the expression patterns of GRAS genes in different ploidy Eucalyptus under cold treatment. This study identified 92 EgrGRAS genes, which were divided into eight subfamilies. Interspecies synteny analysis found that E. grandis and Populus trichocarpa have more syntenic GRAS gene pairs. Chromosome localization analysis revealed that 90 EgrGRAS genes were found to be unevenly distributed across 11 chromosomes. Gene structure analysis found similar intron-exon structures in EgrGRAS genes. Protein motif analysis revealed that proteins within the same subfamily have certain structural similarities. The physical and chemical properties of the proteins encoded by EgrGRAS genes vary, but the ranges of amino acid numbers, molecular weights, and isoelectric points (pI) are similar to those of GRAS proteins from other species. Subcellular localization prediction using software found that 56 members of EgrGRAS family are localized in the nucleus, with a few members localized in the cytoplasm, chloroplasts, and mitochondria. Tobacco subcellular localization experiments verified a nuclear-localized GRAS transcription factor. Cis-acting element analysis predicted that EgrGRAS genes are involved in the growth as well as the response to hormones, light induction, and low-temperature stress. Transcriptome data analysis and quantitative real-time PCR (qRT-PCR) experiments in diploid and triploid Eucalyptus urophylla found that some EgrGRAS genes exhibited upregulated expression under different cold treatment durations, with certain genes from the LISCL, PAT1, and DELLA subfamilies significantly upregulated in triploid Eucalyptus. These EgrGRAS transcription factors may play an important role in Eucalyptus response to cold stress. The study lays a molecular foundation for the breeding of cold-resistant Eucalyptus varieties.